(untitled) (Aporte Santiaguino, 2022)
The objective of the study is to evaluate and determine the levels of risk due to flooding in the Nueva Florida neighborhood of the city of Huaraz. The present investigation is of a quantitative approach with a correlational scope, of the non-experimental cross-sectional type, having evaluated the area comprised of the urban zone between the Paria and Quillcay rivers, with a sample of 116 dwellings. The risk assessment methodology originating from natural phenomena has been used, where the evaluation parameters and hazard susceptibility are analyzed; the vulnerability of exposed elements is analyzed, and the risk levels are determined and zoned. The results obtained from the map of risk levels due to pluvial flooding indicate that there are values ​​of very high risk level (range 0.77 to 0.212) and high risk level (range 0.023 to 0.077). The conclusion of the study indicates that there are very high risk levels and high risk due to pluvial flooding, therefore, the level of acceptability and risk tolerance identified in the Nueva Florida sector has been prioritized as unacceptable, which indicates that Immediate and priority activities must be developed for risk management.